Mitigating path diminution in disjoint multipath routing for mobile ad hoc networks. (25th May 2006) - Abbas, Ash Mohammad; Jain, Bijendra Nath
Design of a disjoint multipath routing protocol in an ad hoc environment is a challenging task. In this paper, we propose a protocol named Vertex Disjoint Multipath Routing (VDMR) to discover multiple node disjoint paths between a given pair of nodes. A major issue in node disjoint multipath routing is path diminution. We propose schemes to mitigate path diminution. We analyse the probability of path diminution in a scheme commonly employed to discover node disjoint paths. We discuss how the probability of path diminution is reduced, using proposed schemes. We observe that VDMR with proposed schemes performs much better than existing multipath routing protocols in the sense that it has a low probability of diminution and high packet delivery ratio.